IJEE 2021
DOI: 10.48165/ijee.2021.57427
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Gap Analysis in Tomato Cultivation in Banda District of Bundelkhand (U.P.)

Abstract: Bundelkhand area of Uttar Pradesh is comprised of seven districts viz., Chitrakoot, Banda, Hamirpur, Mahoba, Jalaun, Jhansi and Lalitpur. The present study was conducted in Banda district of Uttar Pradesh where the vegetable crops are grown by farmers in large areas. Among the eight blocks of Banda, two blocks namely Badokhar Khurd and Mahua were purposively selected. Eight vegetable growing villages (4 from Badokhar Khurd and 4 from Mahua block) based on production potential of the tomato were drawn up and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been observed that technical intervention in food processing and preservation aspects through training programmes increased the knowledge level of small-scale farmers (Meena et al, 2009). Gupta et al (2021) conducted a study on adoption gap analysis in tomato cultivation in Banda District of Bundelkhand (U.P.) and reported 46.40 per cent, 33.10 per cent and 6.53 per cent of technological gap in adoption was observed in harvesting and post-harvest practices in small and marginal farmers respectively.…”
Section: Characterization Of Post-harvest Losses Along the Supply Cha...mentioning
confidence: 99%
“…It has been observed that technical intervention in food processing and preservation aspects through training programmes increased the knowledge level of small-scale farmers (Meena et al, 2009). Gupta et al (2021) conducted a study on adoption gap analysis in tomato cultivation in Banda District of Bundelkhand (U.P.) and reported 46.40 per cent, 33.10 per cent and 6.53 per cent of technological gap in adoption was observed in harvesting and post-harvest practices in small and marginal farmers respectively.…”
Section: Characterization Of Post-harvest Losses Along the Supply Cha...mentioning
confidence: 99%
“…Tomato (Solanum lycopersicum) is one of the most significant vegetable crops in India, ranking second globally in terms of both production and area. China is the world's greatest producer, accounting for 27.8% of total production, followed by India (11.2%) (Kumar et al, 2016;Harisha et al, 2019;Gupta et al, 2021) [12,9,8] . Tomato It is a good source of B, C, and Fe vitamins.…”
Section: Introductionmentioning
confidence: 99%
“…Several causes, including an increase in per capita income, a rise in health consciousness, a shift in farmers' cultivation of better-value vegetables due to higher returns, etc., have contributed to an increase in the area and output of vegetables [2]. In terms of production, China leads the world with a share of 27.8%, followed by India with a share of 11.2% [3][4][5]. Despite India's limited share of the global market (almost 1%), horticulture items are getting increasingly popular [6].…”
Section: Introductionmentioning
confidence: 99%